(untitled) (Ameghiniana, 2025)
Gracilisuchids play a pivotal role in understanding the evolutionary history of Pseudosuchia because of their phylogenetic position between the early suchians and taxa more closely related to Crocodylomorpha. They are currently known for five species registered during the Middle–Late Triassic of China and the Late Triassic of Argentina and Brazil. Here, we describe a new species of gracilisuchid pseudosuchian, Telkaralura coniceti nov. gen. et sp., from the lower Upper Triassic levels of the Chañares Formation of La Rioja Province, northwestern Argentina. The identification of Telkaralura coniceti expands the size range known for gracilisuchids, duplicating the size of the Argentinean Gracilisuchus stipanicicorum, and even surpassing by 25% the size of the largest Brazilian and Chinese species.